Analisa Yuridis Peran Pra Peradilan Dalam Penegakan Hukum Pidana Di Indonesia - Moch Adhitya Rifka Wibowo; Sunarto Sunarto (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The background of this thesis is based on the role of pretrial which functions as a social control mechanism, its implementation in Indonesia still often experiences violations. Therefore, it is necessary to carry out an in-depth analysis to identify the causes of these violations and find solutions to increase the effectiveness of pre-trials in protecting the rights of individuals who are disadvantaged in the application of criminal law in Indonesia. The problem formulation for this thesis is How pre-trial arrangements are made in positive law in Indonesia ? and What is the function and role of pretrial in criminal law enforcement in Indonesia? The research method for this thesis is Normative Juridical where the author examines phenomena related to Pre-Trial from the aspects of Legislation and Legal Principles. The results of this thesis research are that pretrial arrangements in the criminal justice system in Indonesia are regulated in Law No. 8 of 1981 concerning the Criminal Procedure Code. Pretrial, in accordance with Article 1 point (10) in conjunction with Article 77 of the Criminal Procedure Code, is the authority of the district court to examine and decide on several matters, including whether or not an arrest and detention is legal, the termination of an investigation or prosecution, as well as requests for compensation or rehabilitation. Pretrial has an important role in maintaining the balance of law enforcement powers and individual rights in enforcing criminal law. Its main function is to control law enforcement actions and procedures, ensuring justice and compliance with applicable laws. Pretrial is also closely related to the principle of Habeas Corpus which guarantees that a person must not be detained without a valid reason and must be immediately brought to justice. Through pretrial proceedings, individuals can protect themselves from arbitrary actions by law enforcement and seek redress if their rights are violated. Pretrial and the principle of Habeas Corpus together form an important part of the criminal law system in Indonesia which focuses on justice and the protection of human rights.